2014
DOI: 10.1016/j.urology.2014.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Toward Better Use of Bone Scans Among Men With Early-stage Prostate Cancer

Abstract: Objective To evaluate the performance of published guidelines compared to current practice for radiographic staging of men with newly-diagnosed prostate cancer. Materials and Methods Using data from the Michigan Urological Surgery Improvement Collaborative (MUSIC) clinical registry, we identified 1,509 men diagnosed with prostate cancer from March 2012 through June 2013. Clinical data included age, prostate-specific antigen (PSA), Gleason score (GS), clinical T-stage, number of biopsy cores and bone scan (BS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 16 publications
0
39
0
Order By: Relevance
“…Further external validation study of that CART model showed it to have higher specificity and positive predictive value compared to the EAU guideline, while the sensitivity and the NPV of the CART model was comparable with the EAU guideline . In a similar comparative study by Merdan et al , the AUA and NCCN guidelines were found to be relatively similar to the CART model, concluding that adhering to BS in patients with PSA levels of >20 ng/mL and Gleason >7, will yield fewer negative study results, and fewer BS overall. However, in cancer staging tests the primary goal should be to improve sensitivity without ideally sacrificing specificity and therefore, the comparative models also point toward the superiority of the EAU guidelines.…”
Section: Discussionmentioning
confidence: 83%
“…Further external validation study of that CART model showed it to have higher specificity and positive predictive value compared to the EAU guideline, while the sensitivity and the NPV of the CART model was comparable with the EAU guideline . In a similar comparative study by Merdan et al , the AUA and NCCN guidelines were found to be relatively similar to the CART model, concluding that adhering to BS in patients with PSA levels of >20 ng/mL and Gleason >7, will yield fewer negative study results, and fewer BS overall. However, in cancer staging tests the primary goal should be to improve sensitivity without ideally sacrificing specificity and therefore, the comparative models also point toward the superiority of the EAU guidelines.…”
Section: Discussionmentioning
confidence: 83%
“…Patients with PSA concentration >20 ng/mL or a Gleason score ≥8 received a bone scan and a CT scan for staging . Patients with a biopsy result of Gleason score ≥7 underwent radical prostatectomy.…”
Section: Methodsmentioning
confidence: 99%
“…Bone scan. NCCN guidelines and existing literature [28,87] recommend bone scintigraphy if baseline PSA is 20, clinical stage is T2 and PSA is 10, clinical stage is T3 or T4, Gleason score is 8, or any symptoms are suggestive of bone metastases. Essentially all high-risk patients would meet these criteria.…”
Section: Discussion Of Imaging Modalities By Variantmentioning
confidence: 99%